Office Administration Simulation Media to Support Students Skill in the Freedom Curriculum - Andi Basuki; Yuli Agustina; Charlotte Davis (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2023)
This study aims to develop a learning media called Stelar for practical activities to digital manage archives and create digital letters. The learning media can be accessed by three students who act as leaders, secretaries and archivists. In addition, this learning media is also designed to be monitored by the teacher. Thus, the teacher can provide an assessment in the form of numbers and important notes on the work of students. The type of this research was Research and Development using the ADDIE model, namely Analyze, Design, Development, Implementation, Evaluation. Based on the results of the application of learning media to 99 students to work on administrative activities using Stelar media, an average score of 88.5% was obtained. In addition, based on filling out a learner questionnaire to determine the effectiveness of learning media, a score of 90% was obtained. Thus, it can be concluded that the Stelar instructional media can be well accepted and is suitable for use in the learning process of Office Administration students in Indonesia. Keywords: Stelar, office administration, learning media, ADDIE